BUDAYA PERLAWANAN NONVERBAL MELALUI CARA BERPAKAIAN JALANAN PADA CITAYAM FASHION WEEK - Syaharani Alvianita (2023)
This research examines about the culture of resistance embodied in the phenomenon called Citayam Fashion Week (CFW). In previous research stated that the fashion show activity at the zebra crossing was a resistance carried out by CFW youth against the narrative of establishment and appropriateness standards conveyed nonverbally street fashion, while in this study discusses the meaning of nonverbal cultural resistance that is carried out by CFW youth in every activity through the way they dress. Researchers have a focus on expression adolescents through clothing that is considered contrary to culture in DKI Jakarta by using a three-dimensional perspective of artifactual theory such as emotions, behavior, and differentiation to analyze the information obtained in the research. This study aims to obtain the meaning contained in the CFW phenomenon nonverbally using a qualitative approach and supported by method phenomenology so that the discussion obtained can be comprehensive, in-depth, and broad with more comprehensive results. The results of this study reveal the meaning of a culture of resistance for observers and mobilizers, namely CFW youth trying to create support in the process of finding their identity by satisfying themselves in terms of emotions and desires triggered by a lack of a harmonious family and no support from family members and a lack of equal focus media to public expression spaces in several corners of the city.